Introduction to biophotonics - Prasad, Paras N. (Wiley-Interscience, 2003)
Paras Prasad's text provides a basic knowledge of a broad range of topics so that individuals in all disciplines can rapidly acquire the minimal necessary background for research and development in biophotonics. Introduction to Biophotonics serves as both a textbook for education and training as well as a reference book that aids research and development of those areas integrating light, photonics, and biological systems. Each chapter contains a topic introduction, a review of key data, and description of future directions for technical innovation. Introduction to Biophotonics covers the basic.